2009
DOI: 10.1038/npp.2009.75
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants increase neural progenitor cells in the human hippocampus

Abstract: Selective serotonin reuptake inhibitors (SSRIs) and tricyclic antidepressants (TCAs) increase neurogenesis in the dentate gyrus (DG) of rodents and nonhuman primates. We determined whether SSRIs or TCAs increase neural progenitor (NPCs) and dividing cells in the human DG in major depressive disorder (MDD). Whole frozen hippocampi from untreated subjects with MDD (N = 5), antidepressant-treated MDD (MDDT, N = 7), and controls (C, N = 7) were fixed, sectioned and immunostained for NPCs and dividing cell markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
464
4
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 593 publications
(502 citation statements)
references
References 80 publications
31
464
4
3
Order By: Relevance
“…These studies confirm our previous observations of paroxetine on NPC [12]. Several studies have shown that antidepressants increase hippocampal neurogenesis in both animals and humans [39,40] and hippocampal neurogenesis has been suggested to be a key factor in the action of antidepressant drugs [41,42]. Suppression of hippocampal neurogenesis by irradiation prevents the effects of fluoxetine and imipramine [41].…”
Section: Discussionsupporting
confidence: 90%
“…These studies confirm our previous observations of paroxetine on NPC [12]. Several studies have shown that antidepressants increase hippocampal neurogenesis in both animals and humans [39,40] and hippocampal neurogenesis has been suggested to be a key factor in the action of antidepressant drugs [41,42]. Suppression of hippocampal neurogenesis by irradiation prevents the effects of fluoxetine and imipramine [41].…”
Section: Discussionsupporting
confidence: 90%
“…Determinants of hippocampal volume in MDD are not known. Like others (Reif et al, 2006), we did not detect fewer mitotic cells (Boldrini et al, 2009) or neural progenitor cells (NPCs) in the DG postmortem (Boldrini et al, 2009(Boldrini et al, , 2012 in untreated MDD subjects (o58-60 y old) compared to those with no major psychopathology. Notably, blocking (Santarelli et al, 2003) or blunting (Vollmayr et al, 2003) hippocampal proliferation in adulthood is not sufficient to induce depression-like behavior in mice.…”
Section: Introductionmentioning
confidence: 83%
“…The relevance of neurogenesis to depression and antidepressant responses in humans has been examined, although the evidence is limited to a few post-mortem studies. A recent report shows that the rate of new cell birth is significantly increased in depressed subjects receiving antidepressant treatment prior to and at the time of death [25]. However, cell birth was not decreased in untreated depressed subjects.…”
Section: Regulation Of Neurogenesis By Stress and Antidepressant Treamentioning
confidence: 99%